Strategi Pengoptimalan Infrastruktur Pendukung Pariwisata Berkelanjutan - Pratami, Mentari; Gunari, Balqis Febriyantina; Rilansari, Valendya (JURNAL DESTINASI PARIWISATA, 2021)
Banyuwangi Regency is located the easternmost of Java Island and is directly adjacent to Situbondo Regency in the north, the Bali Strait in the east, the Indian Ocean in the south and Jember Regency and Bondowoso Regency in the west. The development of the tourism sector is closely related and dependent on the available infrastructure development. However, the infrastructure related to tourism is inadequate. One of the infrastructures that is still not evenly developed is air transportation. Good transportation will increase visits to tourist areas, and attractive tourist objects will also increase the number of trips. Banyuwangi Regency is known for its domination of tourist destinations in each sub-district consisting of natural tourist destinations or mass tourism. Ijen Tourism Destinations which is one of the leading attractions in Banyuwangi included into (Triangle of Gold) and the Festival international scale contained in Ijen tourist destinations. The fact is that the availability of supporting infrastructure for tourism activities is still minimal in Ijen tourism in Licin District. The purpose of this study examines the strategies to optimize air transport infrastructure in sustainable tourism. The research method is quantitative analysis to calculate airport capacity requirements for the projection of the next 20 years, Qualitative analysis to identify the feasibility of both land and air facilities, as well as airport connectivity analysis which describes the spatial conditions of public transport serving Blimbingsari Airport. This study is expected to help the government or stakeholders in optimizing infrastructure, especially air transportation to support tourism mobility. Keyword: air transport infrastructure, sustainable tourism, tourism mobility